A clinical and molecular genetic study of 112 Iranian families with primary microcephaly. Issue 12 (26th October 2010) - Darvish, H; Esmaeeli-Nieh, S; Monajemi, G B; Mohseni, M; Ghasemi-Firouzabadi, S; Abedini, S S; Bahman, I; Jamali, P; Azimi, S; Mojahedi, F; Dehghan, A; Shafeghati, Y; et al.
Abstract : Background: Primary microcephaly (MCPH) is a genetically heterogeneous disorder showing an autosomal recessive mode of inheritance. Affected individuals present with head circumferences more than three SDs below the age- and sex-matched population mean, associated with mild to severe mental retardation. Five genes ( MCPH1, CDK5RAP2, ASPM, CENPJ, STIL ) and two genomic loci, MCPH2 and MCPH4, have been identified so far. Methods and results: In this study, we investigated all seven MCPH loci in patients with primary microcephaly from 112 Consanguineous Iranian families. In addition to a thorough clinical characterisation, karyotype analyses were performed for all patients. For Homozygosity mapping, microsatellite markers were selected for each locus and used for genotyping. Our investigation enabled us to detect homozygosity at MCPH1 ( Microcephalin ) in eight families, at MCPH5 ( ASPM ) in thirtheen families. Three families showed homozygosity at MCPH2 and five at MCPH6 ( CENPJ ), and two families were linked to MCPH7 ( STIL ). The remaining 81 families were not linked to any of the seven known loci. Subsequent sequencing revealed eight, 10 and one novel mutations in Microcephalin, ASPM and CENPJ, respectively. In some families, additional features such as short stature, seizures or congenital hearing loss were observed in the microcephalic patient, which widens the spectrum of clinical manifestations of mutations in known microcephaly genes. Conclusion: Our results show that the molecular basis of microcephaly is heterogeneous; thus, the Iranian population may provide a unique source for the identification of further genes underlying this disorder.